Upaya Efektifitas Kejaksaan Dalam Pengembalian Asset Negara Dalam Kasus Korupsi - Sefitrios Sefitrios (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
The widespread and systematic crime of corruption is also a violation of the social and economic rights of the community. Therefore, all corruption crimes can no longer be classified as ordinary crimes but have become extraordinary crimes. In an effort to eradicate corruption in Indonesia, the Prosecutor's Office of the Republic of Indonesia continuously works hard with all available capabilities both at the central level (AGO) and at the regional level (High Attorney, District Attorney and District Attorney's Office). In connection with efforts to confiscate and confiscate the proceeds of corruption crimes, it is the most important point in efforts to eradicate corruption in Indonesia, even this is often forgotten by law enforcement where efforts to eradicate corruption are only related to how to punish corruptors. In this paper, the author uses a descriptive qualitative methodology. This paper examines the model of returning assets resulting from corruption crimes in the law enforcement process.